Cloning and primary structure of murine 11 beta-hydroxysteroid dehydrogenase/microsomal carbonyl reductase. - Oppermann, U; Netter, K; Maser, E (1995)
Screening of a mouse liver lambda gt 11 cDNA library with a rat liver 11 beta-hydroxysteroid dehydrogenase cDNA (11 beta-HSDr1A) and subsequent screening with an isolated mouse probe, resulted in the isolation and structure determination of a mouse cDNA encoding an amino acid sequence which is very similar to human and rat 11 beta-hydroxysteroid dehydrogenases (78% and 86% similar, respectively), and also to other known vertebrate 11 beta-hydroxysteroid dehydrogenase structures. Open-reading-frame analysis and the deduced amino acid sequence predict a protein with a molecular mass of 32.3 kDa which belongs to the superfamily of the short-chain dehydrogenase proteins. The amino acid sequence contains two potential glycosylation sites. These data are in agreement with information on the glycoprotein character of the native enzyme. This kind of post-translational modification seems to be a determining factor concerning the equilibrium of the catalyzed 11 beta-dehydrogenation/11-oxo reduction step [Obeid, J., Curnow, K. M., Aisenberg, J. and White, P.C. (1993) Mol. Endocrinol. 7, 154-160; Agarwal, A.K., Tusie-Luna, M.T., Monder, C. and White, P.C. (1990) Mol. Endocrinol. 4, 1827-1832]. After in vitro transcription/translation of the mouse cDNA, immunoprecipitation with anti-(microsomal carbonyl reductase) serum and N-terminal sequence analysis of the purified protein confirms the identity of microsomal 11 beta-hydroxysteroid dehydrogenase with the previously described, microsomal-bound xenobiotic carbonyl reductase [Maser, E. and Bannenberg, G. (1994) Biochem. Pharmacol. 47, 1805-1812], and points to an involvement of the 11 beta-HSD1A isoform in the reductive phase-I metabolism of xenobiotic compounds, besides its endocrinological functions. The alignment and comparison to other hydroxysteroid dehydrogenase forms of the same protein superfamily allows the identification of important residues in the 11 beta-HSD primary structure.